In-situ polymerization self-healing gel polymer electrolyte and preparation method thereof

By polymerizing self-healing gel polymer electrolytes in situ in lithium-ion batteries, and copolymerizing self-healing monomer UPyMA and PEGMA to form a 3D crosslinking network structure, the problem of poor interface contact during electrolyte separation and circulation during bending or folding of traditional lithium-ion batteries is solved, reducing interface impedance and inhibiting the growth of lithium dendrites, and improving the cycling performance and safety of the battery.

CN119542522APending Publication Date: 2025-02-28BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411662896.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When traditional lithium-ion batteries are bent or folded, the electrolyte is easily separated from the electrode material, resulting in internal short circuits and safety problems. The change in electrode volume during the cycle leads to poor interface contact and increases battery impedance.

Method used

Self-healing gel polymer electrolyte was prepared by in-situ polymerization method, and the self-healing monomer UPyMA and PEGMA were introduced to form a 3D cross-linking network structure, reducing interface impedance and inhibiting the growth of lithium dendrites.

Benefits of technology

It effectively reduces the resistance of the battery interface, inhibits the growth of lithium dendrites, improves the cycling performance and safety of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542522A_ABST
    Figure CN119542522A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery preparation, in particular to an in-situ polymerization self-healing gel polymer electrolyte and a preparation method thereof. The preparation method comprises the following steps: S1, synthesizing a self-healing monomer UPyMA; s2, preparing a precursor solution; s3, a self-healing monomer UPyMA is fully dissolved in the precursor solution; s4, injecting the precursor solution into a PP diaphragm, and assembling into a battery; and S5, preparing the self-healing gel polymer electrolyte PEGUPY with relatively low interface resistance with the battery through an in-situ thermal polymerization method. The in-situ polymerization self-healing gel polymer electrolyte with excellent electrochemical performance and interface performance is successfully prepared by introducing the self-healing monomer UPyMA. The electrolyte not only solves the problems of the traditional gel polymer electrolyte, but also provides an effective solution for the improvement of a new-generation gel electrolyte system of a flexible electronic device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium ion battery preparation, and in particular to an in-situ polymerized self-healing gel polymer electrolyte and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are considered to be the main energy storage devices for portable and wearable electronic devices due to their high energy density, high operating voltage, low self-discharge effect and no memory effect. However, traditional lithium-ion batteries are mostly rigid structures, and the electrolyte is easily separated from the electrode material when bent or folded, resulting in internal short circuits and even safety problems in the battery. Gel polymer electrolytes composed of polymers and lithium salts have the advantages of good flexibility, thermal stability and processability, and have become the main choice for safe electrolytes. The preparation of gel electrolytes includes casting method, phase separation method, electrospinning method and in-situ polymerization method. Among them, the in-situ polymerization method is the direct polymerization of the precursor solution into a film in the battery, which has the advantages of low production cost, seamless interface contact and strong processability, and is more suitable for large-scale production of gel electrolytes.

[0003] In gel polymer electrolytes prepared by in-situ polymerization, impurity particles that penetrate into the electrode / electrolyte interface can lead to irregular lithium deposition, resulting in damage and cracks at the electrode-electrolyte interface. Once cracks occur, they will aggravate the growth of lithium dendrites. Although in-situ polymerization can ensure good interface contact, changes in the electrode volume will occur during the battery cycle, resulting in a decrease in the interface contact effect and an increase in battery impedance. Self-healing refers to the ability to spontaneously recover from mechanical damage, which is an important survival feature in nature. Endowing gel polymers with self-healing properties helps to extend the service life of the polymer and repair microcracks, which can effectively inhibit the formation of lithium dendrites. Therefore, the preparation of flexible, electrochemically superior self-healing gel polymer electrolytes by in-situ polymerization is of great significance in inhibiting lithium dendrites and improving battery safety. Summary of the invention

[0004] In view of the poor interface contact caused by the growth of lithium dendrites at room temperature and the repeated changes in electrode volume during the cycle of traditional gel polymer electrolytes, this application provides an in-situ polymerizable self-healing gel polymer electrolyte and its preparation method, which successfully reduces the interface impedance by introducing self-healing monomer copolymerization, while inhibiting the growth of lithium dendrites and improving the battery's cycle performance. At the same time, the in-situ polymerized self-healing gel polymer electrolyte prepared by this application solves the problems of lithium dendrite growth at room temperature and unstable battery cycle performance of in-situ polymerized PEGMA / LiPF6 gel polymer electrolytes.

[0005] In a first aspect, the present application provides a method for preparing an in-situ polymerized self-healing gel polymer electrolyte, using the following technical solution: A method for preparing an in-situ polymerization self-healing gel polymer electrolyte comprises the following steps: S1. Select appropriate self-healing raw materials, double-bond monomers and solvent systems to synthesize the self-healing monomer UPyMA; S2, washing by vacuum filtration, and further removing the solvent by vacuum drying to obtain the self-healing monomer UPyMA; S3, selecting appropriate free radical in-situ polymerization monomers, crosslinking agents, initiators and an appropriate amount of electrolyte to prepare a precursor solution; S4, fully dissolving the self-healing monomer UPyMA in the precursor solution; S5, injecting the precursor solution into the PP separator to assemble the battery; S6. A PEGMA and UPyMA copolymer containing a 3D cross-linked network was constructed by in situ thermal polymerization to prepare a self-healing gel polymer electrolyte PEGUPY with low interface resistance with the battery.

[0006] By adopting the above technical scheme, the present application provides an in-situ polymerization self-healing gel polymer electrolyte and a preparation method thereof, which successfully reduces the interfacial impedance by introducing self-healing monomer copolymerization, and inhibits the growth of lithium dendrites, thereby improving the cycle performance of the battery. Select suitable self-healing raw materials, double-bond monomers and solvent systems to synthesize the self-healing monomer UPyMA (S1): This step is the basis of the entire preparation process, and the selection of suitable self-healing raw materials and double-bond monomers is crucial for subsequent polymerization reactions. By synthesizing the self-healing monomer UPyMA, the foundation is laid for the subsequent construction of a gel polymer electrolyte with self-healing function. Vacuum filtration washing and vacuum drying are used to further remove the solvent to obtain the self-healing monomer UPyMA (S2). This step is intended to remove the solvent and other impurities that may remain in the synthesis process, and ensure that the obtained self-healing monomer UPyMA has high purity and quality. This is crucial for subsequent polymerization reactions and the performance of the electrolyte. Select suitable free radical in-situ polymerization monomers, crosslinking agents, initiators and appropriate amounts of electrolytes to configure the precursor solution (S3): This step involves the selection and proportioning of a variety of chemical substances to form a precursor solution suitable for polymerization. The selection and ratio of these chemicals will directly affect the performance of the final gel polymer electrolyte. Fully dissolve the self-healing monomer UPyMA in the precursor solution (S4): This step is to mix the previously synthesized self-healing monomer UPyMA with the precursor solution to fully dissolve it. This helps to achieve the self-healing function in the subsequent polymerization process. Inject the precursor solution into the PP diaphragm and assemble it into a battery (S5) This step is to inject the prepared precursor solution into the PP diaphragm and then assemble it into a battery. This is a key step to achieve in situ polymerization, because in this process, the precursor solution will undergo polymerization reaction inside the battery to form a gel polymer electrolyte. A PEGMA and UPyMA copolymer containing a 3D cross-linked network is constructed by in situ thermal polymerization, thereby preparing a self-healing gel polymer electrolyte PEGUPY with a small interface resistance with the battery (S6): This step is the core of the entire preparation process. Through the in situ thermal polymerization method, the precursor solution is polymerized inside the battery to form a PEGMA and UPVMA copolymer containing a 3D cross-linked network. This copolymer has low interfacial resistance and good self-healing properties, can effectively inhibit the growth of lithium dendrites, and improve the cycle performance of the battery. In summary, this application successfully prepared an in-situ polymerized self-healing gel polymer electrolyte with excellent electrochemical properties and interfacial properties through a series of innovative technical means and process improvements. This electrolyte not only solves the problems existing in traditional gel polymer electrolytes, but also provides a solution for the improvement of a new generation of gel electrolyte systems for flexible electronic devices.

[0007] Preferably, in step S1, the self-healing raw material is 2-amino-4-hydroxy-6-methylpyrimidine; the double bond monomer is isocyanoethyl methacrylate; and the solvent is dimethyl sulfoxide.

[0008] Preferably, in step S2, the washing process condition is to wash with acetone and methanol three times respectively, and the vacuum drying process condition is to put it in a vacuum oven and dry it at 30° C. for 4 hours.

[0009] Preferably, in step S3, the free radical in situ polymerization monomer is 2,2,2-trifluoromethylacrylate; the cross-linking agent is pentaerythritol tetraacrylate; the initiator is azobisisobutyronitrile; and the electrolyte is an electrolyte obtained by dissolving 1M LiPF6 in EC:DEC=1:1.

[0010] Preferably, in step S4, the mass concentration of the self-healing monomer UPyMA fully dissolved in the precursor solution is 3%.

[0011] Preferably, in step S5, the method of injecting the precursor solution into the PP diaphragm is to add 40 microliters of the precursor solution on both sides of the PP diaphragm; and the assembling into a battery means standing the assembled battery for 6-8 hours to allow the precursor solution to fully infiltrate.

[0012] Preferably, in step S6, the in-situ thermal polymerization method is to place the assembled battery in a 70°C oven for 6 hours to allow the monomers to fully copolymerize, thereby completing the in-situ preparation of PEGUPY.

[0013] In a second aspect, the present application provides an in-situ polymerized self-healing gel polymer electrolyte, which adopts the following technical solution: As a general technical concept, the present application also provides the above-mentioned in-situ polymerization self-healing gel polymer electrolyte, which is prepared by the above-mentioned preparation method of in-situ polymerization self-healing gel polymer electrolyte.

[0014] By adopting the above technical scheme, the in-situ polymerized self-healing gel polymer electrolyte prepared by the present application solves the problems of lithium dendrite growth and unstable battery cycle performance at room temperature in the in-situ polymerized PEGMA / LiPF6 gel polymer electrolyte. In view of the interface safety issues existing in the in-situ polymerized gel electrolyte, the present application has developed a new electrolyte system with high safety performance, excellent electrochemical performance, and excellent interface performance, which effectively solves the problems of low ionic conductivity, severe polarization during charge and discharge, and poor cycle stability of the currently developed PEGMEA-based gel polymer electrolyte at room temperature. Compared with traditional in-situ polymerized gel polymer electrolytes, the self-healing gel polymer electrolyte of the present application effectively reduces the interface impedance, can inhibit dendrite growth and improve battery cycle stability, and provides a solution for the improvement of the new generation of gel electrolyte systems for flexible electronic devices.

[0015] In summary, the beneficial technical effects of this application are: 1. Reduce interface impedance: By introducing the self-healing monomer UPyMA and copolymerizing it with PEGMA to form a 3D cross-linked network structure, the resistance of the battery interface is effectively reduced. This low-resistance interface helps to improve the charge and discharge efficiency and cycle stability of the battery. 2. Inhibit the growth of lithium dendrites: The 3D cross-linked network structure in the self-healing gel polymer electrolyte can effectively inhibit the growth of lithium dendrites, thereby reducing the risk of internal short circuit caused by dendrite penetration and improving the safety performance of the battery.

[0016] 3. Improved cycle performance: Due to the reduction of interfacial impedance and the inhibition of lithium dendrite growth, the battery performance is more stable during the cycle process, and the cycle life is significantly improved. This is especially important for application scenarios such as electric vehicles and portable electronic devices that require long-term stable operation.

[0017] 3. Structural stability: The coating layer with reverse dual gradient element distribution can effectively inhibit the volume expansion of silicon during the charging and discharging process, reduce the material breakage and shedding during the cycle process, and thus extend the service life of the battery.

[0018] 4. Solve the problem of low ionic conductivity at room temperature: Compared with traditional PEGMEA-based gel polymer electrolytes, the self-healing gel polymer electrolyte of the present application has higher ionic conductivity at room temperature, which means that the battery can also maintain a good working condition under normal temperature conditions.

[0019] 5. Reduce polarization during charging and discharging: High ionic conductivity helps reduce the polarization of the battery during charging and discharging, thereby improving the battery's energy efficiency and output power.

[0020] 6. Improved cycle stability: By optimizing the electrolyte system, the cycle stability of the battery at different temperatures and current densities is improved, allowing the battery to work stably under a wider range of working conditions.

[0021] 7. Provide improvement solutions for flexible electronic devices: The self-healing gel polymer electrolyte of this application is not only suitable for traditional lithium-ion batteries, but also particularly suitable for the application of flexible electronic devices, such as wearable devices, flexible screens, etc., providing them with a safer and more reliable electrolyte solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments: Figure 1 The electrochemical impedance spectra of stainless steel-stainless steel button cells assembled from the precursor solutions of Examples 1 to 3 of the present invention and Comparative Example 1 at 0.1-105 Hz; wherein Test Example 1 in the figure corresponds to Example 1, Test Example 2 corresponds to Example 2, and Test Example 3 corresponds to Example 3; Figure 2 The lithium-lithium symmetric battery assembled from the precursor solutions of Example 1 and Comparative Example 1 at 0.1 mA cm -2 The time-voltage curve below; Figure 3 It is the time-voltage curve of the lithium-lithium iron phosphate full battery assembled from the precursor solutions of Example 1 of the present invention and Comparative Example 1 at 0.2C; Figure 4 It is the first cycle discharge specific capacity-voltage curve of the lithium-lithium iron phosphate full battery assembled from the precursor solutions of Example 1 of the present invention and Comparative Example 1 at 0.2C. DETAILED DESCRIPTION

[0023] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0024] Preparation Example 1: Preparation of UPyMA Monomer 2 g of 2-amino-4-hydroxy-6-methylpyrimidine was dissolved in 80 mL of dimethyl sulfoxide (DMSO) and stirred at 150°C for 10 minutes to completely dissolve the white powder. The reaction bottle was transferred to room temperature, 2.64 g of isocyanoethyl methacrylate was added, and the reaction was continued at room temperature for 2 hours. A large amount of white solid gradually appeared in the reaction bottle. The reaction solution was vacuum filtered to remove the solvent, and the white solid was washed 3 times with acetone and methanol respectively, and then transferred to a vacuum oven at 30°C for 4 hours to obtain UPyMA monomer.

[0025] Example 1 47.75g of 2,2,2-trifluoromethylacrylate, 1.5g of pentaerythritol tetraacrylate (PETEA) and 0.75g of thermal initiator azobisisobutyronitrile (AIBN) were dissolved in 50g of electrolyte (1M LiPF6 dissolved in EC / DEC, v / v=1:1), and stirred at 300r / min for 1h. Then, 3.09g of UPyMA monomer prepared in Preparation Example 1 was added, and stirred at 400r / min for 5h to make the UPyMA monomer evenly dispersed, so as to obtain a precursor solution containing self-healing monomers. When assembling the battery, the precursor solution was injected into the battery assembled with a polypropylene (PP) diaphragm (40 microliters of the precursor solution was added to both sides of the PP diaphragm). After the battery was assembled, it was left to stand for 7 hours to allow the precursor solution to fully infiltrate, and then the battery was placed in a 70°C oven for 6h to allow the monomers to fully copolymerize, thus completing the in-situ preparation of PEGUPY (abbreviated as PEGUPY-3).

[0026] Example 2 47.75g of 2,2,2-trifluoromethylacrylate, 1.5g of pentaerythritol tetraacrylate (PETEA) and 0.75g of thermal initiator azobisisobutyronitrile (AIBN) were dissolved in 50g of electrolyte (1M LiPF6 dissolved in EC / DEC, v / v=1:1), and stirred at 300r / min for 1h. Then, 5.26g of UPyMA monomer prepared in Preparation Example 1 was added, and stirred at 400r / min for 5h to make the UPyMA monomer evenly dispersed, so as to obtain a precursor solution containing self-healing monomers. When assembling the battery, the precursor solution was injected into the battery assembled with a polypropylene (PP) diaphragm (40 microliters of the precursor solution was added to each side of the PP diaphragm). After the battery was assembled, it was left to stand for 7 hours to allow the precursor solution to fully infiltrate, and then the battery was placed in a 70°C oven for 6h to allow the monomers to fully copolymerize, thus completing the in-situ preparation of PEGUPY (abbreviated as PEGUPY-5).

[0027] Example 3 47.75g of 2,2,2-trifluoromethylacrylate, 1.5g of pentaerythritol tetraacrylate (PETEA) and 0.75g of thermal initiator azobisisobutyronitrile (AIBN) were dissolved in 50g of electrolyte (1M LiPF6 dissolved in EC / DEC, v / v=1:1), and stirred at 300r / min for 1h. Then, 7.53g of UPyMA monomer prepared in Preparation Example 1 was added, and stirred at 400r / min for 5h to make the UPyMA monomer evenly dispersed, so as to obtain a precursor solution containing self-healing monomers. When assembling the battery, the precursor solution was injected into the battery assembled with a polypropylene (PP) diaphragm (40 microliters of the precursor solution was added to both sides of the PP diaphragm). After the battery was assembled, it was left to stand for 7 hours to allow the precursor solution to fully infiltrate, and then the battery was placed in a 70°C oven for 6h to allow the monomers to fully copolymerize, thus completing the in-situ preparation of PEGUPY (abbreviated as PEGUPY-7).

[0028] Comparative Example 1 47.75g of 2,2,2-trifluoromethylacrylate, 1.5g of pentaerythritol tetraacrylate (PETEA) and 0.75g of thermal initiator azobisisobutyronitrile (AIBN) were dissolved in 50g of electrolyte (1M LiPF6 dissolved in EC / DEC, v / v=1:1), and stirred at 300r / min for 1h to obtain a precursor solution containing a self-healing monomer. When assembling the battery, the precursor solution was injected into the battery assembled with a polypropylene (PP) diaphragm (40 microliters of the precursor solution was added to each side of the PP diaphragm). After the battery was assembled, it was allowed to stand for 7 hours to allow the precursor solution to fully infiltrate, and then the battery was placed in a 70°C oven for 6h to allow the monomers to fully copolymerize, thus completing the in-situ preparation of PEGUPY (PEGMEA for short).

[0029] Application Example 1: Assemble the stainless steel-stainless steel button cell battery: Stainless steel is used as the positive and negative electrodes, polypropylene is used as the diaphragm, the precursor solution configured in the above-mentioned Examples 1 to 3 and Comparative Example 1 is added, and a 2025-type battery shell is used. The stainless steel-stainless steel button battery is assembled in the order of negative electrode shell, stainless steel sheet, precursor solution, diaphragm, precursor solution, stainless steel sheet, gasket, spring sheet, and positive electrode shell.

[0030] The zinc-zinc symmetrical button cells assembled in each embodiment and comparative example were subjected to electrochemical impedance spectroscopy test on an electrochemical workstation in a frequency range of 0.1 Hz-10 5 Hz. It was carried out on Chenhua CHI660E, and the test temperature was maintained at 30℃.

[0031] Figure 1The stainless steel-stainless steel battery assembled with the precursor solution in Examples 1 to 3 and Comparative Example 1 was operated at 0.1 Hz to 10 5 Electrochemical impedance spectroscopy at Hz frequency. Figure 1 It can be seen that when the self-healing monomer copolymer is not used, the bulk impedance of the gel polymer electrolyte is 14.16Ω. When different contents of UPyMA monomer are used for copolymerization, the bulk impedance of the gel polymer electrolyte is reduced, among which, when the UPyMA monomer is used in an appropriate amount (Example 1), it can be reduced to 7Ω. This shows that the introduction of an appropriate amount of UPyMA monomer significantly reduces the bulk impedance of the gel electrolyte.

[0032] Application Example 2: Assemble Li-Li Button Cells: A lithium sheet with a thickness of 0.4 mm was used as the positive and negative electrodes, polypropylene was used as the separator, the precursor solution configured in the above Example 1 and Comparative Example 1 was added, and a 2025-type battery shell was used to assemble a lithium-lithium symmetrical button battery in the order of negative electrode shell, lithium sheet, precursor solution, separator, precursor solution, lithium sheet, gasket, spring sheet, and positive electrode shell.

[0033] experiment: The lithium-lithium symmetric button cells assembled in Example 1 and the comparative example were subjected to electrochemical tests. -2 The constant current charge and discharge test was carried out at a current density of 1.5 %. It was carried out on the Xinwei battery test system and the test temperature was maintained at 30°C.

[0034] Cyclic overpotential: Figure 2 The symmetrical battery assembled using the precursor solutions in Example 1 and Comparative Example 1 at 0.1 mAcm -2 The current density is 0.1 mAh cm -2 The time-voltage curve under the capacity of Figure 2 It can be seen that without using UPyMA monomers, the overpotential of the lithium-lithium symmetric battery reached 154mV after 300h of cycling. When using UPyMA monomers with a mass concentration of 3%, the overpotential of the symmetric battery remained stable at around 67mV. This shows that the introduction of an appropriate amount of UPyMA monomers significantly reduced the overpotential of the symmetric battery.

[0035] Application Example 3: Assembling Li-FePO4 full battery: Lithium iron phosphate is used as the positive electrode active material, a lithium sheet is used as the negative electrode, polypropylene is used as a separator, the electrolyte configured in the above Example 1 and Comparative Example 1 is added, and a 2025-type battery shell is used. The lithium-lithium iron phosphate button battery is assembled in the order of negative electrode shell, lithium sheet, precursor solution, separator, precursor solution, positive electrode active material, gasket, spring sheet, and positive electrode shell.

[0036] experiment: Electrochemical tests were performed on the full batteries assembled in Example 1 and Comparative Example 1. The tests were performed on a Xinwei battery testing system, with a battery voltage range of 2.5 to 4.0 V and a test temperature of 30°C.

[0037] Cycle life: from Figure 3 and Figure 4 It can be seen that under the current density of 0.2C, the in-situ polymerized gel polymer battery containing the precursor solution of Example 1 can be stably cycled for 200 cycles, and the battery's first cycle discharge capacity is 143.7 mAh g -1 , its capacity remained at 72.44%; while the capacity of the battery assembled from the precursor solution of comparative example 1 decayed rapidly, and the capacity retention was only 79% after 80 cycles. This shows that the introduction of the self-healing monomer UPyMA can effectively improve the cycle stability of the battery, indicating its successful application as a copolymer monomer in gel polymer electrolytes.

[0038] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing an in-situ polymerization self-healing gel polymer electrolyte, characterized in that: The following steps are involved: S1. Select appropriate self-healing raw materials, double-bond monomers and solvent systems to synthesize the self-healing monomer UPyMA; S2, further removing the solvent by vacuum filtration, washing, and vacuum drying to obtain the self-healing monomer UPyMA; S3, selecting appropriate free radical in-situ polymerization monomers, crosslinking agents, initiators and an appropriate amount of electrolyte to prepare a precursor solution; S4, fully dissolving the self-healing monomer UPyMA in the precursor solution; S5, injecting the precursor solution into the PP separator to assemble the battery; S6. A PEGMA and UPyMA copolymer containing a 3D cross-linked network was constructed by in situ thermal polymerization to prepare a self-healing gel polymer electrolyte PEGUPY with low interface resistance with the battery.

2. The method for preparing an in-situ polymerization self-healing gel polymer electrolyte according to claim 1, characterized in that: In step S1, the self-healing raw material is 2-amino-4-hydroxy-6-methylpyrimidine; the double bond monomer is isocyanoethyl methacrylate; and the solvent is dimethyl sulfoxide.

3. The method for preparing an in-situ polymerization self-healing gel polymer electrolyte according to claim 1, characterized in that: In step S2, the washing process condition is to wash with acetone and methanol three times respectively, and the vacuum drying process condition is to put it in a vacuum oven and dry it at 30°C for 4 hours.

4. The method for preparing an in-situ polymerization self-healing gel polymer electrolyte according to claim 1, characterized in that: In step S3, the free radical in situ polymerization monomer is 2,2,2-trifluoromethylacrylate; the crosslinking agent is pentaerythritol tetraacrylate; the initiator is azobisisobutyronitrile; and the electrolyte is an electrolyte obtained by dissolving 1M LiPF6 in EC:DEC=1:

1.

5. The method for preparing an in-situ polymerization self-healing gel polymer electrolyte according to claim 1, characterized in that: In step S4, the mass concentration of the self-healing monomer UPyMA fully dissolved in the precursor solution is 3%.

6. The method for preparing an in-situ polymerization self-healing gel polymer electrolyte according to claim 1, characterized in that: In step S5, the method of injecting the precursor solution into the PP diaphragm is to add 40 microliters of the precursor solution on both sides of the PP diaphragm; and the assembling into a battery means standing the assembled battery for 6-8 hours to allow the precursor solution to fully infiltrate.

7. The method for preparing an in-situ polymerization self-healing gel polymer electrolyte according to claim 1, characterized in that: In step S6, the in-situ thermal polymerization method is to place the assembled battery in a 70°C oven for 6 hours to allow the monomers to fully copolymerize, thereby completing the in-situ preparation of PEGUPY.

8. An in-situ polymerized self-healing gel polymer electrolyte, characterized in that: The self-healing gel polymer electrolyte is prepared by the preparation method of the in-situ polymerization self-healing gel polymer electrolyte according to any one of claims 1 to 7.